Fluoropolymers-mediated efficient biomacromolecule drug delivery - Tingting Song; Yuemei Gao; Mingjie Song; Jia Qian; Huaqing Zhang; Jianping Zhou; Yang Ding (Elsevier, 2022)
Biomacromolecule drugs of nucleic acids and proteins/peptides have occupied growing share of global pharmaceutical market, but their biomedical application faces substantial challenges in lacking of safe and effective delivery vehicles due to the high molecular weight and the sensitive structure. Because of the unique physicochemical and biological properties of hydrophobicity and lipophobicity, superior assembly performance, desirable chemical stability, and biological inertness, fluoropolymers are a modular solution to these problems as an ideal delivery vehicle of biomacromolecules. In the review, we discuss how to endow the polymer with "fluorine magic" as fluoropolymers and summarized the recent advances of fluoropolymers specifically tailored to the delivery challenges of biomacromolecule drugs, including stability, serum tolerance, membrane permeability, endosomal escape of nucleic acids and intercellular delivery of proteins/peptides. Moreover, this work concludes the application of fluoropolymers-mediated biomacromolecule drug delivery in cancer therapy. Finally, we discuss the opportunities, challenges and further perspectives of fluoropolymers for the delivery of biomacromolecule drugs, aiming to facilitate further development of fluoropolymers in biomedical application.